The use of propolis for mastitis control - Laranjo, Marta (2019)
Propolis is a resinous mass produced by honeybees for the protection of the honeycomb. Propolis has become very popular in Europe due to its antibacterial activity. Recently, propolis activity against bacterial biofilms was reported. Mastitis control greatly depends on the use of antimicrobials. Antimicrobial resistance and bacterial ability to produce biofilm increase microbial survival and contribute to pathogens’ persistence in the farm. Furthermore, the transfer of resistance genes from mastitis causing pathogens to bacteria belonging to the human natural microbiota fully justifies the search for alternative products with antimicrobial activity. The aim of this study was to assess propolis components accountable for bactericidal and antibiofilm activities against Staphylococcus spp. isolated from the milk of sheep and goats with mastitis. Ten propolis batches (seven from Brazil and three from Portugal) were collected in different regions and were used to produce 30% propolis ethanol extracts (PEE). Total phenolics, flavonoids, anthocyanins and condensed tannins contents were assessed. Thirty-five Staphylococcus aureus and 104 coagulase-negative staphylococci (CNS) were analysed for in vitro susceptibility to PEE and minimum bactericidal concentration (MBC) was performed with a 96-pins microplate replicator. These PEE were also assessed for biofilm formation inhibition and biofilm disruption on 44 biofilm producing Staphylococcus isolates. To identify the propolis components, which are probably associated with antimicrobial and antibiofilm activities, statistical analyses were performed. Total phenolics content varied from 67.62 to 365.42 mg GAE/g extract, flavonoids content from 54.82 to 140.6 mg QE/g extract, anthocyanins content between not detected and 8.39 mg/g extract, and condensed tannins content between 36.92 and 3766.16 mg ECC/g DP extract. All 139 staphylococci analysed (100%) showed to be susceptible to all PEE, but Brown4, with concentrations varying between 0.026 and 13.37 mg/mL. Concerning antibiofilm activity, nine PEEs inhibited biofilm formation in most of the 44 biofilm-forming isolates. The mean inhibition percentage for each PEE, varied between 33.5 and 80.2%. Regarding biofilm disruption, all ten PEE partially or totally destroyed the biofilm produced by all 44 staphylococci isolates. The mean PEE activity on biofilm disruption varied between 28.4 and 79.5%. According to these results, propolis deserves to be considered for the control of mastitis.